Self-Determined Stories : The Indigenous Reinvention of Young Adult Literature - Suhr-Sytsma, Mandy (Book collections on Project MUSE., 2019)
"As the first book-length study of Indigenous-authored Young Adult literature, this project advances conversations in Native Studies about the meaning of Indigenous sovereignty and expands conceptualizations of power dynamics and genre in YA Literary Studies"--Provided by publisher.